1998
DOI: 10.1046/j.1365-2664.1998.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term recolonization patterns of ants in Western Australian rehabilitated bauxite mines with reference to their use as indicators of restoration success

Abstract: 1.  The return of invertebrate animals to rehabilitated mine pits is desirable for the re‐establishment of ecosystem functioning. A long‐term ant monitoring programme is reported over 14 years in a jarrah Eucalyptus marginata forest control plot and in three bauxite mine pits, one of which had been left unvegetated, one planted with marri trees E. calophylla and the other seeded with mixed native plant species. 2.  The results confirm published findings for the first 2 years of the succession that seeding wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
0
9

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(140 citation statements)
references
References 18 publications
4
127
0
9
Order By: Relevance
“…A total of 33 species were found in the three rehabilitated plots and 20 were found in the forest reference. A number of other species have previously been sampled in these plots but are no longer present, indicating the high degree of flux in species composition, a feature which has already been described in Majer and Nichols (1998). Overall ant abundance was slightly higher in the unplanted and planted plots than in the forest, but seeded plot values were considerably lower (Additional file 1).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…A total of 33 species were found in the three rehabilitated plots and 20 were found in the forest reference. A number of other species have previously been sampled in these plots but are no longer present, indicating the high degree of flux in species composition, a feature which has already been described in Majer and Nichols (1998). Overall ant abundance was slightly higher in the unplanted and planted plots than in the forest, but seeded plot values were considerably lower (Additional file 1).…”
Section: Resultsmentioning
confidence: 77%
“…These trends appeared to be reflected in the abundance and variety of other invertebrate groups. Majer and Nichols (1998) continued with the sampling through to 14 years and found that, although ant species richness had increased in all mine plots, the findings from the first 2 years had been upheld, although in the last 6 years of sampling the richness of ants in the unrevegetated plot had started to move toward levels found in the other two mined plots as volunteer vegetation had naturally established in the area. Differences between the seeded and planted plots had also started to lessen, although ant assemblage composition in all mined plots still exhibited marked differences to that present in the forest reference.…”
Section: The Long-term Studymentioning
confidence: 98%
“…Semut mempunyai korelasi yang kuat dengan variabel ekosistem yakni vegetasi, iklim mikro, tanah, dan fauna tanah lainnya (Shahabudin, 2011). Secara teknis pengambilan sampel semut relatif mudah dilakukan dan secara taksonomi mudah diidentifikasi sehingga semut dapat digunakan untuk membantu memahami kaidah ekologi, biomonitoring untuk tujuan konservasi dan pengelolaan hutan (Majer dan Nichols, 1998).…”
Section: Pendahuluanunclassified
“…Peta hutan lindung Sirimau Ambon. ditemukan semut yang mampu hidup dalam kurun waktu lima tahun (Majer dan Nichols, 1998). Faktor lingkungan sangat mempengaruhi kehadiran semut pada perkebunan kakao di Brasil karena faktor kandungan nitrogen pada tanaman yang ditanam dan sistem pengelolaan tanah yang dkerjakan dimana semut mengalami perubahan kehadiran, vitalitas dan memberikan respon terhadap praktek pengelolaan tanah (Pecarevic dkk., 2010).…”
Section: Pendahuluanunclassified
“…Ceres, Viçosa, v. 61, Suplemento, p. 800-807, nov/dez, 2014 1999; Ribas et al, 2012). Elas foram estudadas em diversos ambientes, como: áreas de reabilitação de minas, na Austrália (Majer & Nichols, 1998), na África do Sul (Majer & Kock, 1992) e no Brasil (Oliveira & Della Lucia, 1992;Majer, 1996;Santos et al, 2008); em áre-as com metais pesados (Ribas et al, 2012); em áreas de cultivo agrícola (Peck et al, 1998); em avaliação de distúrbio em florestas tropicais (Marinho et al, 2002;Delabie et al, 2006;Leal et al, 2012;Miranda et al,2013) e, ainda, em áreas cultivadas tratadas com inseticidas (Couto et al, 2010;Pereira et al 2010) e herbicidas .…”
Section: Insetos Como Potenciais Bioindicadores De Qualidade Ambientalunclassified